2023
DOI: 10.1186/s44149-023-00070-2
|View full text |Cite|
|
Sign up to set email alerts
|

Antibody seropositivity and endemicity of chikungunya and Zika viruses in Nigeria

Abstract: Mosquito-borne infections are of global health concern because of their rapid spread and upsurge, which creates a risk for coinfections. chikungunya virus (CHIKV), an arbovirus disease transmitted by Aedes aegypti or A. albopictus, and malaria, a parasitic disease transmitted by Anopheles gambiae, are prevalent in Nigeria and neighbouring countries, but their burden and possible coinfections are poorly understood. In this study, we investigated the antibody seropositivity and endemicity of chikungunya and Zika… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…Visual inspection of the Galbraith plot represented four outlier studies. The outlier studies were identified as Mac 2023 [32], Leonhard 2021 [54], Mehta 2018 [65], and da Costa 2017 [71] (Figure 4).…”
Section: Outlier and Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Visual inspection of the Galbraith plot represented four outlier studies. The outlier studies were identified as Mac 2023 [32], Leonhard 2021 [54], Mehta 2018 [65], and da Costa 2017 [71] (Figure 4).…”
Section: Outlier and Sensitivity Analysismentioning
confidence: 99%
“…The arboviruses are transmitted by the same vectors, and their simultaneous circulation is observed in numerous places worldwide [29][30][31][32][33][34][35]. Moreover, there have been earlier reports of concurrent infections, some of which have been linked to mortality [36,37].…”
Section: Introductionmentioning
confidence: 99%